VIDEO BASED TEACHING OF AVIATION ENGLISH - Petrashchuk, Olena; Skypalska, Olena (Proceedings of National Aviation University (archive), 2014)
The article deals with teaching Aviation English using video. Compliance with new ICAO languagerequirements has become part of the professional qualification. The article looks at some benefits and potentialchallenges associated with using video materials in the classroom during language training of air traffic controllers(ab initio).